INDONESIAN FAMILY ECONOMIC PRODUCT BRAND COMPETITION - Pane, Dewi; El Fikri, Miftah (Quantitative Economics Journal, 2023)
This research was conducted to determine how the influence of Brand Image (X1), Product Quality (X2), Promotion (X3), and Price (X4) on Purchase Decision (Y) of the BuKrim brand detergent product. The population in this research did not know with certainty, but the number of samples used was 97 respondents who were calculated by the Zikmund formula. The sampling technique used was accidental sampling. The research was conducted in Medan City. The research was conducted in 2020. This research used quantitative data processed with the SPSS version 24.0 application with multiple linear regression models. The data source used was the primary data taken directly from respondents. The results showed that brand image, product quality, promotion, and price had a positive and significant effect both partially and simultaneously on purchasing decisions for BuKrim brand detergent products. The product quality variable was the most dominant variable in influencing purchasing decisions. Brand image, product quality, promotion, and price contributed 86.9% in the formation of purchasing decisions. Brand image, product quality, promotion, and price had a very strong relationship to purchasing decisions.